Hybrid fuzzy and support vector machine based blur detection technique - Kaur, Sukhamrit; Vijay Kumar Banga, Dr. (International Journal of Engineering and Technology, 2018)
The main objective of our research work is to acquire good quality of an image which is blurred. Therefore, in this research our effort is to propose an advanced algorithm to improve the quality of an image by eliminate the blur in an efficient manner. In this paper, two types of blurred images (i.e., Gaussian blur and out of focus) are used. Deblurring techniques are mostly used to eradicate the blur of an image using different methods & parameters. To reimburse blur different types of methods like algorithm, filtering techniques, fuzzy based approach, support vector machine are used. Blur detection methods are used to eradicate the blur from a blurred section of an image which is caused by the out of focus blur and Gaussian blur.Â Â